Distribuição de espécies ao longo de um gradiente altitudinal em floresta ombrófila densa montana - Silva, Mônica Taires Rodrigues da (2021)
The floristic composition and species distribution of plant communities are influenced by several factors, such as climatic, spatial and environmental, contributing to the high diversity in tropical forests. Thus, we aimed to evaluate the influence of the altitudinal gradient on the distribution of species in a Montana Dense Ombrophilous Forest. To this end, we used a database from floristic surveys of the arboreal and regenerating strata of the Santa Marta valley in the Caparaó National Park, in which, in previous studies, seven permanent plots were demarcated at different altitudinal levels. We calculated the phytosociological parameters of the studied community and then, to identify clusters of plots with greater species similarity, we floristically compared the plots using the unweighted average clustering method (UPGMA) based on the Bray-Curtis similarity index. We performed the Indicator Species Analysis (ISA) to obtain the species that characterize the formed floristic clusters and used the Redundancy Analysis (RDA) to verify the influence of environmental factors on the vegetation. Our database totaled 5086 individuals distributed in 63 botanical families. The species with the highest importance value (VI) were Euterpe edulis Mart. (16.18%) and Psychotria vellosiana Benth. (14.01%). We verified the formation of two groups with greater floristic similarity: plots between 1,112 and 1,302 m and plots between 1,319 and 1,550 m of altitude. The variables with the greatest influence on the vegetation were altitude, temperature, organic matter, potential acidity and potential cation exchange capacity, and the RDA result explained 87.37% of the variation in floristic composition along the valley. We conclude that the species that make up the plant community of the Santa Marta valley exhibit a heterogeneous distribution pattern along the altitudinal gradient and are influenced by the joint action of environmental variables, which allows for the existence of high diversity in the studied area.